CHECKING THE ORIGINALITY OF DIGITAL PICTURES - HAMBALIK, Alexander (Trends in education, 2010)
The article contains basic information about the ways of studying the originality of digitally stored pictures without comparing them to their originals. The possibilities described help in identification of forgeries and plagiarisms in school and publishing practice.
Keywords: digital picture without alteration; original of the digital picture; plagiarism; forgery.